SAFE: Design Takes on Risk - Tanne, Janice Hopkins (BMJ Publishing Group Ltd., 2005)
An exhibition at the Museum of Modern Art, 11 West 53rd Street, New York, NY 10019, until 2 January 2006. Admission $20 www.moma.org/exhibitions/2005/safe.html Rating: ★★★★